Marvel vs. Jack Kirby: o impacto do modelo work-for-hire no legado dos criadores de quadrinhos e sua análise sob o regime jurídico brasileiro - Santos, Antônio Vitor Alber dos (Brasil, 2025)
This study analyzes the historical and legal relationship between comic book creators and major entertainment corporations, focusing on the impact of the *work-for-hire* regime on copyright law. The research investigates how artists, often responsible for creating iconic characters and narratives, were undervalued and deprived of recognition and financial benefits from their work. Using key cases such as the disputes involving Jack Kirby and Marvel Comics, as well as Jerry Siegel and Joe Shuster, the creators of Superman, the study demonstrates the consequences of the work-for-hire model and the application of U.S. copyright laws, particularly the Copyright Act of 1976 and its later amendments. Through a bibliographic review, documentary analysis, and case studies, the research explores the tensions between major publishers and their creators, addressing the contractual conditions during the Golden Age of Comics and the contemporary conflicts related to the massive exploitation of intellectual properties in cinema and other media. Furthermore, initiatives aimed at breaking away from this model, such as the foundation of Image Comics in the 1990s, are highlighted, as they sought to ensure greater creative and economic autonomy for artists. The findings reveal the persistence of abusive practices in the relationship between corporations and creators, even in the face of legislative changes. Moreover, the similarities between the contracted work modalities in the United States and Brazil were analyzed, elucidating the omission of national regulations on this matter. As a result, the judiciary has relied on case law that analogously applies the Industrial Property Law. The study concludes that, although progress has been made, such as posthumous recognition and financial settlements for the heirs of artists like Kirby, there is still an urgent need to review copyright policies to properly value creators' contributions and address historical imbalances. This research aims to contribute to the debate on intellectual property, power dynamics in the cultural industry, and the importance of fairer policies for recognizing artistic work.